Hypertrophic pachymeningitis, IgG4-related disease: case report - Gunter Gerson; Carlos Eduardo L. Soares; Amanda R. Rangel; Gabriel C. L. Chagas; Daniel R. F. Távora; Kellen P. Fermon
ABSTRACT The IgG4-related disease (IgG4-RD) is a systemic disease recently characterized as an inflammatory condition generally related to the increase in serum IgG4 levels, a subclass of immunoglobulins (IgG) which corresponds to less than 6% of the total serum IgG, with singular histopathological features. The involvement of the central nervous system is rare and may be isolated or associated with other organs, mimicking tumors. Commonly, it involves the hypophysis, presenting hypophysitis as the main manifestation, but it can also affect the dura mater, presenting as IgG4-related hypertrophic pachymeningitis (IgG4-RHP). Neurological manifestations occur as a result of mass effect, typically due to vascular or nervous structures compression, resulting in functional deficits according to the anatomical site of the lesion. The main histopathological features are dense lymphoplasmacytic infiltrate, fibrosis arranged, at least focally, in a storiform pattern, and obliterative phlebitis, associated with increased numbers of IgG4+ plasma cells or an increased IgG4/IgG ratio in tissue. In this disease, the serum IgG4 levels are usually increased. The objective of this article is to report the case of a 37-year-old male patient who presented a pulsatile headache associated with diplopia and blurred vision. After radiological, histopathological and immunohistochemical studies, the diagnosis of IgG4-RHP was confirmed, besides presenting a literature review about IgG4-RD and IgG4-RHP.